Incorporating Motor Aspects in a Competence-based Syllabus for Second Grade English Class in SD Muhammadiyah Jagalan - Cisya Dewantara Nugraha; Dian Ayu Septiani Wiwitan (JLA (Jurnal Lingua Applicata), 2019)
This paper aims to describe the development and implementation of competence-based syllabus of English in the second grade class of SD Muhammadiyah Jagalan. The research data were collected through direct observation and interviews with teachers and headmaster in SD Muhammadiyah Jagalan. Quotes from several books and references were used to support the analysis. The result showed that there are five stages to incorporate motor aspect in developing a competence-based syllabus, namely implementing the principles, formulating the set of procedures, implementing the development process, and formatting and modelling the developed syllabus based on KBK. The developed syllabus was then implemented in the class. The result showed that the developed syllabus brought positive impact for the students’ learning process in class. The impact include the increasing attention of students to the material explained by the teacher in the class, the building up of student’s self-confidence, and the growing interest of students to participate in the class when the teacher gives assignments.